Human Rights Violation: Its impact on the mental well-being of LGBTI students in a South African rural-based university - Mavhandu-Mudzusi, A.H.; Sandy, P.T. (South African Journal of Higher Education, 2017)
This paper reports on Human Rights violation, and its impact on the mental well-being of lesbian, gay, bisexual, transgender and intersex students in a South African rural based university. A qualitative multi-method approach was adopted, underpinned by interpretative phenomenological analysis. Data were collected using semi-structured individual interviews (N=20) and focus group interviews (n=4x5). The data were analysed thematically using interpretative phenomenological analysis. The results of the study indicate that university employees and heterosexual students violate lesbian, gay, bisexual, transgender and intersex students` rights. The violation of human rights has implications for the mental well-being of the studied population.